2012
DOI: 10.1371/journal.pone.0050117
|View full text |Cite
|
Sign up to set email alerts
|

Improved Glycaemia Correlates with Liver Fat Reduction in Obese, Type 2 Diabetes, Patients Given Glucagon-Like Peptide-1 (GLP-1) Receptor Agonists

Abstract: Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are effective for obese patients with type 2 diabetes mellitus (T2DM) because they concomitantly target obesity and dysglycaemia. Considering the high prevalence of non-alcoholic fatty liver disease (NAFLD) in patients with T2DM, we determined the impact of 6 months’ GLP-1 RA therapy on intrahepatic lipid (IHL) in obese, T2DM patients with hepatic steatosis, and evaluated the inter-relationship between changes in IHL with those in glycosylated haemoglobin (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(189 citation statements)
references
References 36 publications
6
179
3
Order By: Relevance
“…Finally, in another study, improved glucose control correlated with liver fat reduction in obese T2DM patients given GLP-1 receptor agonists exenatide or liraglutide for 6 months [60] . There is growing evidence that incretin-based therapies have beneficial effects on hepatocytes; however, further study analysis are needed to assess the long-term effect of incretin-based therapies on NAFLD [19] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, in another study, improved glucose control correlated with liver fat reduction in obese T2DM patients given GLP-1 receptor agonists exenatide or liraglutide for 6 months [60] . There is growing evidence that incretin-based therapies have beneficial effects on hepatocytes; however, further study analysis are needed to assess the long-term effect of incretin-based therapies on NAFLD [19] .…”
Section: Discussionmentioning
confidence: 89%
“…Exenatide has been shown to improve glucose control in patients with T2DM and concomitant NAFLD [59][60][61] or NASH [62] . A recently published animal study suggested that SIRT 1 , a NAD+-dependent protein deacetylase that is considered as a crucial regulator in hepatic lipid homeostasis, mediates the effect of exenatide on ameliorating hepatic steatosis [63] .…”
Section: Hepatic Safetymentioning
confidence: 99%
“…Liver lipid was measured non-invasively using proton magnetic resonance spectroscopy ( 1 H-MRS) as previously described [31][32][33] . NAFLD was defined as intrahepatocellular lipid content (IHCL) > 5.5% measured by 1 H-MRS. Three voxels of interest were identified in the liver avoiding ducts and vasculature and the mean value taken after data were processed independently.…”
Section: Methodsmentioning
confidence: 99%
“…As part of studies powered to detect changes in glycaemic control in patients with type 2 diabetes and NAFLD, they caused a reduction in intrahepatic lipid as measured by MRS in addition to reductions in body weight and improved glycaemic control (98). In a separate analysis of type 2 diabetic patients treated with Liraglutide, there was a dose-dependent but non-significant improvement in hepatic steatosis, measured by liver-spleen attenuation ration as well as improvements in abnormal liver function tests (99).…”
Section: Glucagon-like Peptide-1mentioning
confidence: 99%